2021
DOI: 10.1038/s41597-021-00907-w
|View full text |Cite
|
Sign up to set email alerts
|

Time series of useful energy consumption patterns for energy system modeling

Abstract: The analysis of energy scenarios for future energy systems requires appropriate data. However, while more or less detailed data on energy production is often available, appropriate data on energy consumption is often scarce. In our JERICHO-E-usage dataset, we provide comprehensive data on useful energy consumption patterns for heat, cold, mechanical energy, information and communication, and light in high spatial and temporal resolution. Furthermore, we distinguish between residential, industrial, commerce, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…• JERICHO-E-usage dataset. This is an energy consumption time series dataset provided in [26]. This dataset covers the hourly energy consumption of 38 regions in German with different energy categories (e.g., residential, industrial, commerce, and mobility sectors) in the whole year of 2019.…”
Section: Appendix a Additional Experimentsmentioning
confidence: 99%
“…• JERICHO-E-usage dataset. This is an energy consumption time series dataset provided in [26]. This dataset covers the hourly energy consumption of 38 regions in German with different energy categories (e.g., residential, industrial, commerce, and mobility sectors) in the whole year of 2019.…”
Section: Appendix a Additional Experimentsmentioning
confidence: 99%
“…where T w is the length of weekly segment along time axis. The reason for considering the long-term correlations is that the work of [36] and [37] have found that electricity usage shows weekly patterns periodically in one certain period . The framework of the proposed MG-ASTGCN is illustrated in Fig.…”
Section: A Spatial-temporal Correlations Extraction Via Mg-astgcnmentioning
confidence: 99%
“…The great success of DNNs in such domains can in part be explained by the huge amount of available data to train complex models. Following the trend, the last few years have also seen an explosion in the amount of time series data of various modalities such as electrocardiogram [3], power consumption [4], human motion [5] and satellite images [6] among others. Due to its wide range of applications, time series analysis has attracted researchers who developed deep learning-based models for time series clustering [7], averaging [8], forecasting [9] and classification [10].…”
Section: Introductionmentioning
confidence: 99%